Seeking Peace in the Wake of War : Europe, 1943-1947 - Romijn, Peter; Kott, Sandrine; Wieviorka, Olivier, 1960-; Hoffmann, Stefan-Ludwig (Book collections on Project MUSE., 2015)
When World War II ended, Europe was in ruins. Yet politically and socially, the years between 1943 and 1947 were a time of dramatic reconfigurations that proved to be foundational for the making of today's Europe. This volume homes in on the crucial period from the beginning of the end of Nazi rule to the advent of the Cold War. It demonstrates how the everyday experiences of Europeans during these five years shaped the transition of their societies from war to peace. The essays explore these reconfigurations on different scales and levels with the purpose of enhancing our understanding of how wars end.